Creative Lockdown? A Daily Diary Study of Creative Activity During Pandemics - Karwowski, Maciej; Zielińska, Aleksandra; Jankowska, Dorota M.; Strutyńska, Elzbieta; Omelańczuk, Iwona; Lebuda, Izabela (Frontiers in Psychology, 2021)
The COVID-19 pandemic is influencing our lives in an enormous and unprecedented way. Here, we explore COVID-19-lockdown’s consequences for creative activity. To this end, we relied on two extensive diary studies. The first, held in March 2019 (pre-pandemic), involved 78 students who reported their emotions and creativity over two weeks (927 observations). The second, conducted in March 2020 (during the pandemic and lockdown), involved 235 students who reported on their emotions, creativity, and the intensity of thinking and talking about COVID-19 over a month (5,904 observations). We found that compared to 2019, during the lockdown, students engaged slightly, yet statistically significantly more in creative activities. Analysis of diaries collected during the pandemic also showed that days when students spent more time discussing or searching for information about COVID-19, were characterized by higher creative activity, yet also mixed emotions. We discuss potential explanations of these unexpected results along with future studies directions.